Kazanga – Ethnicité en Afrique entre État et Tradition - Van Binsbergen, Wim (Afrika Focus, 1993)
The production of cultural forms at the interface between a rural-based tradition and the state is a familiar aspect of ethnicity in contemporary Africa. This paper seeks to identify some of the characteristics of thisprocess, whose products are too often misunderstood, and cherished, as ’authentic’ forms of ’tradition’. Highlighting the role of ethnic brokers, of the modern mass media, and of a model of commoditifled ’performance ’ as an aspect of contemporary electronic mass culture, the argument explores the production of expressive culture in the context of the Kazanga cultural association and its Kazanga annual festival among the Nkoya people of central western Zambia since the early 1980s, against the background of Nkoya ethnicity and Nkoya expressive and court culture since the 19th century. KEY WORDS: associations, brokers, commoditification, dance, ethnicity, festivals, music, Nkoya, state, Zambia